Barriers to technology integration in Bhutanese secondary science classrooms - Wangdi, Norbu; Kanasa, Harry; Kanasa, Harry; Amy Kim, Eun-Ji (Bhutan Journal of Research and Development, 2025)
Integrating digital technology in education is considered an indispensable tool for 21st-century classrooms; however, its use in the Bhutanese classrooms is in its infancy. This study investigated the barriers to integrating technology in the Bhutanese secondary science classrooms. Informed by Ertmer’s framework of barriers to technology integration, the study employed a sequential mixed-methods approach. The study recruited secondary science teachers (n = 135) teaching grades nine to twelve through snowball sampling from 42 secondary schools nationwide. The data for the study were collected using an online questionnaire and virtual one-on-one interviews. The study revealed that limited technology resources, such as computers and reliable internet access, as well as a lack of formal training for teachers, pose significant barriers to the integration of technology in secondary science classrooms. The study recommends that the Ministry of Education and Skill Development (MoESD) eliminate the identified barriers to facilitate the effective integration of technology, thereby enhancing students’ learning outcomes.